2014
DOI: 10.1371/journal.pone.0110940
|View full text |Cite
|
Sign up to set email alerts
|

The Orthopaedic Trauma Patient Experience: A Qualitative Case Study of Orthopaedic Trauma Patients in Uganda

Abstract: The disability adjusted life years (DALYs) associated with injuries have increased by 34% from 1990 to 2010, making it the 10th leading cause of disability worldwide, with most of the burden affecting low-income countries. Although disability from injuries is often preventable, limited access to essential surgical services contributes to these increasing DALY rates. Similar to many other low- and middle-income countries (LMIC), Uganda is plagued by a growing volume of traumatic injuries. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…Our findings are supported by a study of orthopedic trauma patients in Uganda where the authors identified social, economic, and health care system factors affecting injuries [11]. Economic loss was common, which also had implications for the Ugandan patients' families because most were breadwinners with multiple dependents.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our findings are supported by a study of orthopedic trauma patients in Uganda where the authors identified social, economic, and health care system factors affecting injuries [11]. Economic loss was common, which also had implications for the Ugandan patients' families because most were breadwinners with multiple dependents.…”
Section: Discussionsupporting
confidence: 74%
“…Structural or environmental factors like accessing care and navigating the health system played a role in injury care in Uganda, however, transportation and terrain were the major obstacles mentioned in the present study [11]. Traditional medicine was a common alternative to hospital treatment in Nigeria and preferred among some Ghanaians, but we did not observe the same utilization patterns or attitudes toward traditional medicine in our study [10,12].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Populations in these regions are predominantly rural,4 and the few dollars required for a bus ride to the hospital are often an insurmountable barrier to care 5. Those patients that successfully navigate through the barriers to access surgery in low-income countries are frequently greeted with lengthy queues, overcrowding and poor facilities as well as shortage of trained personnel 6…”
mentioning
confidence: 99%
“…However, due to the lack of or a limited number of powered orthopedic drills, they tend to wait for days to have surgery or they do not have it done at all. 5 There have been attempts to overcome this challenge of unavailability of drills with the use of fabric and surgical chuck adapters that can be sterilized, coupled to industrial hardware drills. However, the challenge still remains throughout the world due to the inability to commercialize this laudable innovation.…”
Section: Introductionmentioning
confidence: 99%